Reviewing Dependability Issues and Suitable Solutions for Emerging Wireless Sensor Networks Applications - Rolim, Carlos Oberdan; Freitas, Edison Pignaton de; Heimfarth, Tales; Pereira, Carlos Eduardo; Geyer, Cláudio F. R.; Ferreira, Armando Morado; Wagner, Flávio Rech; Larsson, Tony (Anais do Workshop de Testes e Tolerância a Falhas (WTF), 2011)
Some Wireless Sensor Networks applications can be considered safe critical due to the important impact caused in occurrence of their malfunctioning. Motivated by this issue, a research area in dependability applied to WSN is gaining strength. As highly distributed systems, WSN present a number of issues that have to be handled in order to achieve a dependable behavior. These issues are stressed considering the current sophisticated WSN, composed by static and/or mobile nodes. This paper proposes a review of the main problems and trends in the area of dependability for WSN, aiming to find suitable solutions to the problems faced by emerging WSN composed of static and mobile sensor nodes. Such applicability is analyzed for an application scenario of area surveillance.